Phrenic nerve injury occurring from removal of a chest drain in a 26-year-old male - Hayler, Raymond R.; Selvendran, Selwyn T.; Langcake, Mary E. (International Surgery Journal, 2022)
Chest tubes are a common procedure performed worldwide, especially in trauma. Complications arising can be from the result of insertion, incorrect position, or infection. Phrenic nerve injury has previously been a rare complication, found usually in neonates. We described the unusual and previously unreported case of a 26-year-old male who suffered a right phrenic nerve injury as a result of a misplaced chest tube, occurring not in insertion but during removal. The chest tube was placed initially emergently during a polytrauma for bilateral pneumothoraces. With removal, sudden tachypnea was noted with negative workups for pulmonary embolus or reaccumulation of pneumothorax. There was ongoing reduction of spirometry volumes and a persistently raised right hemidiaphragm, with suspicion for bronchial plugging and resorption atelectasis. Following respiratory review, the diagnosis was confirmed with chest wall fluoroscopy with a ‘Sniff test’. With good recovery of overall respiratory function, the patient was discharged with conservative management.